Developmental screening and early intervention in a childcare setting for young children at risk for autism and other developmental delays: A feasibility trial. Issue 9 (26th June 2019) - Gulsrud, Amanda; Carr, Themba; Williams, Justin; Panganiban, Jonathan; Jones, Felica; Kimbrough, Jackie; Shih, Wendy; Kasari, Connie
Abstract: Efforts to decrease disparity in diagnosis and treatment for under‐resourced children with developmental delays, such as autism spectrum disorder, have led to increased interest in developing programs in community settings. One potential setting that has already demonstrated feasibility in conducting universal screening is the childcare setting. The current study conducted developmental screening in a total of 116 children ages 16–80 months of age in an urban low‐income community childcare center. Parents of 20 children who screened positive were enrolled in the intervention phase of the study, where children received a staff‐delivered targeted early intervention or a waitlist control condition. Given the small and imbalanced sample sizes, confidence intervals from mixed effect models were used to measure changes across time for each group. Of the children who received treatment, there was an average increase in child initiated joint engagement, symbolic play, and language use. This study provides initial feasibility data for the implementation of a screening and early intervention program to service a predominantly low‐resource and ethnically diverse population within the childcare system in a large metropolitan city. Autism Res 2019, 12: 1423–1433 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Identifying and delivering treatment services for young children with developmental delays, such as autism spectrum disorder, may be most successful in community settings, especially for those children from under‐resourced areas. This study found preliminary evidence that the childcare setting is a good place to conduct screening and deliver early interventions for children at risk for autism and other developmental delays.